Assisted Ventilation in Patients with Acute Respiratory Distress Syndrome: Lung-distending Pressure and Patient–Ventilator Interaction. (July 2015) - Doorduin, Jonne; Sinderby, Christer A.; Beck, Jennifer; van der Hoeven, Johannes G.; Heunks, Leo M. A.
Abstract : Background: In patients with acute respiratory distress syndrome (ARDS), the use of assisted mechanical ventilation is a subject of debate. Assisted ventilation has benefits over controlled ventilation, such as preserved diaphragm function and improved oxygenation. Therefore, higher level of "patient control" of ventilator assist may be preferable in ARDS. However, assisted modes may also increase the risk of high tidal volumes and lung-distending pressures. The current study aims to quantify how differences in freedom to control the ventilator affect lung-protective ventilation, breathing pattern variability, and patient–ventilator interaction. Methods: Twelve patients with ARDS were ventilated in a randomized order with assist pressure control ventilation (PCV), pressure support ventilation (PSV), and neurally adjusted ventilatory assist (NAVA). Transpulmonary pressure, tidal volume, diaphragm electrical activity, and patient–ventilator interaction were measured. Respiratory variability was assessed using the coefficient of variation of tidal volume. Results: During inspiration, transpulmonary pressure was slightly lower with NAVA (10.3 ± 0.7, 11.2 ± 0.7, and 9.4 ± 0.7 cm H2 O for PCV, PSV, and NAVA, respectively; P < 0.01). Tidal volume was similar between modes (6.6 [5.7 to 7.0], 6.4 [5.8 to 7.0], and 6.0 [5.6 to 7.3] ml/kg for PCV, PSV, and NAVA, respectively), but respiratory variability was higher with NAVA (8.0 [6.4 to 10.0], 7.1 [5.9 to 9.0], and 17.0 [12.0 to 36.1] % for PCV, PSV, and NAVA, respectively; P < 0.001). Patient–ventilator interaction improved with NAVA (6 [5 to 8] % error) compared with PCV (29 [14 to 52] % error) and PSV (12 [9 to 27] % error); P < 0.0001. Conclusion: In patients with mild-to-moderate ARDS, increasing freedom to control the ventilator maintains lung-protective ventilation in terms of tidal volume and lung-distending pressure, but it improves patient–ventilator interaction and preserves respiratory variability. Abstract : Twelve patients with mild-to-moderate acute respiratory distress syndrome were ventilated in a randomized order with three ventilation modes: pressure control ventilation, pressure support ventilation, and neurally adjusted ventilatory assist. Lung-protective ventilation was maintained to a similar degree in all study arms; the results are hypothesis generating for using assisted ventilation in patients with acute respiratory distress syndrome after the first 48 h of therapy, which might include paralysis.Supplemental Digital Content is available in the text.